The political economy of convergence - Shin, Dong Hee (Javnost (Ljubljana), 2008)
Drawing upon qualitative data from stakeholders in convergence in Korea, this study traces the process of convergence in terms of politics, regulation, and policy, and examines how the stakeholders' interests are aligned and coordinated in the process of convergence in Korea. Using actor network theory, the study relates the socio-technological construction of Korea's strategy for convergence reform. Key research questions are: (1) What strategy has Korea adopted, (2) What social and political factors have influenced strategy formulation, and (3) How different interests have stabilised ideologies in which actors formulate their strategies based on their interests. Despite the dynamics of interactions, the actor-network around convergence has not been effectively stabilised yet, as the politics of convergence is complex and marked by paradoxical features.
Keywords: Južna Koreja; sociologija komunikacij; mass media; množični mediji; telecommunication; telekomunikacije; digitalne telekomunikacije